PENGARUH FREKUENSI AUDIT ATAS LAPORAN KEUANGAN HISTORIS TERHADAP KEANDALAN STRUKTUR PENGENDALIAN INTERN PADA PERUSAHAAN DI KOTA DENPASAR - YADNYANA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007), 2007)
This research is intended to reveal the effect of the auditing frequency tothe historical financial statement on the capability of internal control structure ofbusiness enterprises in Denpasar. This research is also carried out to gain theempirical evidence of the effect of auditing frequency to the historical financialstatement on the capability of internal control structure without paying attentionto other variables. A series of statistical tests have been done by using singleregression analysis, Product Moment Pearson correlation analysis, and FAnova.The result shows that the effect of auditing frequency to the historicalfinancial statement has a significant influence on the capability of internal controlstructure. Furthermore, a test to an independent variable (X) is performed to findout whether an independent variable (X) could explain the changing variation todependent variable (Y). This test results R2 = 0,508, which means that theindependent variable (X) could explain the changing variation in the independentvariable (Y) to the extent of 50,8%. The rest of it, which is 49,2% could beexplained by other factors excluded in this model.
Keywords: auditing frequency, historical